2008
DOI: 10.1139/b08-040
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Brassica nigra to Pieris brassicae herbivory

Abstract: Black mustard, Brassica nigra (L.) Koch, is a wild annual species found throughout Europe and fed on by larvae of the large cabbage-white butterfly, Pieris brassicae L. We examined the impact of herbivory from P. brassicae, a gregarious herbivore, on B. nigra grown from wild seed collected locally. In greenhouse studies, the response of B. nigra to four herbivore densities in two developmental stages of the plant was quantified by measuring leaf damage, plant height, days to flowering, silique number, and seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Our results agree with several studies demonstrating the ability of plants to fully compensate for simulated grazing in grazingdominated systems (e.g., Biondini et al, 1998;Blatt et al, 2008). As in most drylands of the Middle-East region, the Yatir forest, and especially its annual plant communities, has a long history of intensive livestock grazing (Perevolotsky and Seligman, 1998), which might have selected for differential responses of plants to grazing under different productivity levels (Osem et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Our results agree with several studies demonstrating the ability of plants to fully compensate for simulated grazing in grazingdominated systems (e.g., Biondini et al, 1998;Blatt et al, 2008). As in most drylands of the Middle-East region, the Yatir forest, and especially its annual plant communities, has a long history of intensive livestock grazing (Perevolotsky and Seligman, 1998), which might have selected for differential responses of plants to grazing under different productivity levels (Osem et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…These studies, and the small scale field study of Strauss et al [62] on wild radish are not inconsistent with our fitness results if plants in these protected conditions rarely suffered mortality or if seed output was calculated only from plants that lived to reproduce (rather than including zero seed production for plants that died as juveniles). Blatt et al [63] suggested that an increase in stress through multiple attacks by herbivores, simultaneous damage by pathogens, or poor growing conditions may curb tolerance to herbivory and allow herbivores to exert measurable fitness effects on plants. In our study, early mortality resulting in zero seed set and aborted flowers resulting in plants with few seeds were important factors in explaining the overall very strong effects of herbivory (or release from herbivory) on average lifetime fitness per plant.…”
Section: Herbivory and Plant Fitnessmentioning
confidence: 99%
“…Females lay batches of eggs on their host plant in the spring. Caterpillars emerge and feed on the host plant as a group until the late fourth or early fifth instar when they disperse over the plant (Blatt et al 2008). At the end of the fifth instar, they begin wandering off the plant in search of a pupation site.…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the fifth instar, they begin wandering off the plant in search of a pupation site. The number of eggs per batch can vary from seven to 105 (Kristensen 1994;Blatt et al 2008), but on average there are between 30 and 50 eggs per batch (Feltwell 1982). It is an oligophagous pest with a wide host range and is known to infest 83 species of food plants belonging to Cruciferae.…”
Section: Introductionmentioning
confidence: 99%